Transforming government to think and act GAD handbook on gender and development training - Masilungan, Elena (National Commission on the Role of Filipino Women, 2003)
Contents: General pointers on how to develop, run and evaluate a GAD training program. Synopsis of modules. Modules to equip planners, budget officers and technical personnel. Glossary of concepts and terms in GAD.